Speed and agility of 12- and 14-year-old elite male basketball players - Jakovljevic, S. T.; Karalejic, M. S.; Pajic, Z. B.; Macura, M. M.; Erculj, F. F. (The Journal of Strength and Conditioning Research, 2012)
The aims of this study were (a) to identify and compare the speed and agility of 12- and 14-year-old elite male basketball players and (b) to investigate relations between speed and agility for both age groups of basketball players, to help coaches to improve their work. Sixty-four players aged 12 (M = 11.98 years, SD = 0.311) and 54 players aged 14 (M = 14.092 years, SD = 0.275) were tested. Three agility tests: agility t-test, zigzag agility drill, and agility run 4 × 15 m and 3 speed tests: 20-m run, 30-m run, and 50-m run were applied. Fourteen-year-old players achieved significantly better results in all speed and agility tests compared with 12-year-old players. The correlation coefficient (r = 0.81, p = 0.001) showed that 12-year-old players have the same ability in the 30- and 50-m runs. The other correlation coefficient (r = 0.59, p = 0.001) indicated that 20- and 30-m runs had inherently different qualities. The correlation coefficients between agility tests were <0.71, and therefore, each test in this group represents a specific task. In 14-year-old players, the correlation coefficients between the speed test results were <0.71. In contrast, the correlation coefficients between the agility tests were >0.71, which means that all the 3 tests represent the same quality. During the speed training of 12-year-old players, it is advisable to focus on shorter running distances, up to 30 m. During the agility training of the same players, it is useful to apply exercises with various complexities. In speed training of the 14-year-old players, the 30- and 50-m runs should be applied, and agility training should include more specific basketball movements and activities.